The Development and Characterization of Herbal Kulfi (Ice Cream) Using Tulsi, Ginger, and Clove: Development Kulfi (Ice Cream) using herb and spices - Khushal Solanki, Rekha Rani, Gaurav Kumar Gaur (Indian Journal of Dairy Science, 2023)
Herbs and spices are used for imparting flavor, the aroma of the products and also possess various therapeutic properties like anti-stress, anti-hypertensive, anti-tumor, anti-oxidant, anti-microbial, and anti-inflammatory properties. The present study was aimed to develop herbal kulfi using tulsi paste, ginger juice, and clove extract and the effects of the addition of herbs on its compositional, physicochemical properties, nutritional parameters, sensory attributes, and microbial quality. Initial trials were conducted to adjudge the most acceptable levels using tulsi paste (2.5%, 5.0% and 7.5%), ginger juice (2.0%, 3.0% and 4.0%) and clove extract (2.0%, 3.0% and 4.0%). An optimized herbal kulfi was developed using 2.5% tulsi paste, 2.0% ginger juice, and 4.0% clove extract. The kulfi prepared without any addition of tulsi, ginger, and clove was treated as control. The optimized herbal kulfi reported a fat content of 12.0%, protein 3.53 %, total solids 42.80%, ash 1.0233%, carbohydrate 23.04%. The developed herbal kulfi reported 10.01% anti-oxidant activity and total phenolic content of 56.96 mg GAE/100g. The products possess a good level of anti-oxidant and total phenolic content. The herbal kulfi conforms to the FSSA requirements for ‘kulfi’. The standard plate count was found 3.85 cfu/g. The yeast and mold and coliform count were absent in the product as per FSSA standard.